The Jatinangoriense Herbarium as Learning Innovations within the Independent Learning Independent Campus (MBKM) - Irawan, Budi; Eneng Nunuz Rohmatullayaly (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The Jatinangoriense Herbarium is a teaching herbarium managed by the Biosystematics and Molecular Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Padjadjaran University. It stores approximately 8,000 specimens, including collections of angiosperms, ferns, algae, fungi, seed collections, simplicia, and carpology. The herbarium serves as a facility for learning, research, community service, and plant identification services. In line with the Merdeka Belajar Kampus Merdeka (MBKM) program, the presence of this teaching media plays an essential role in supporting the program as a means of developing digital teaching media and courses that focus on the competence of biocurators. This qualitative research employs the 4D model with four stages: define, design, develop, and disseminate. The result is an instructional video on the techniques and management of the herbarium, which serves as one of the teaching materials in the Collection and Management of Biological Specimens course. Additionally, the MBKM program facilitates off-campus students by using digital learning facilities, encouraging universities to develop virtual museums and herbaria that can be widely accessed as sources of knowledge. The Bachelor’s Degree Program in Biology at the Faculty of Mathematics and Natural Sciences, Padjadjaran University, provides students with the opportunity to learn and practice the development of a virtual herbarium through the Digitalization of Biological Objects course, utilizing various specimens from the Jatinangoriense Herbarium.